A study on the impact of the design and features of a software application on crowdsourcing - Hao, Anran (2019)
Crowdsourcing, which refers to outsourcing tasks to a large group of people (i.e. the crowd), has been an increasingly popular approach to problem-solving. It is potentially valuable to the public sector, offering distinct advantages such as lower costs and solution diversity. However, as the success of crowdsourcing relies on the active participation of the public, designing an effective incentive mechanism remains a major challenge for implementers. This project explores the use of gamification, which is to apply game design features in a non-game context, to encourage participation in a public crowdsourcing mobile application. The application enables citizens to access and share information on public access Automated External Defibrillators (AEDs) in Singapore. It uses the crowdsourcing approach to tackle two public problems in the country, namely creation and maintenance of a comprehensive, up-to-date national AED database, and insufficient emergency preparedness of the general public. Gamification of the prototype was designed based on Deci & Ryan’s (2000) Self-Determination Theory (SDT). The prototype was implemented using Android Studio, Google Map API and Google Firebase. To study the effect of such a design approach, a comparative user survey was conducted against a non-gamified baseline version, involving a total of 160 participants. Results suggest that while both the versions were perceived as having good usability, the gamification design has increased users’ intrinsic motivation. The gamified crowdsourcing application is also associated with a significantly stronger intention to use the application, which implies that gamification can be applied in public crowdsourcing to encourage participation effectively. The implications and future directions of the study are also discussed.